Accuracy of amplitude integrated EEG in a neonatal cohort. Issue 3 (5th May 2010) - Evans, E; Koh, S; Lerner, JT; Sankar, R; Garg, M
Abstract : Objective: To determine the sensitivity and specificity of amplitude integrated electroencephalogram (aEEG) compared to simultaneous standard electroencephalogram (sEEG) for seizure detection and background discontinuity. Design: Prospective paired cohort. Setting: Tertiary academic neonatal intensive care unit. Patients: Infants were recruited from 2005 to 2008. Neonates requiring sEEG were recruited for simultaneous aEEG. Interventions: Following sEEG and aEEG, seizures were recorded as present or absent, and background was recorded as normal or discontinuous in each format. Main outcome measures: Presence of at least one seizure during recording. The background activity was reported as normal or discontinuous. Discontinuity of brain activity was further ranked as mild, moderate or severe. Results: 51 sEEG and aEEG studies were completed. 44 studies were analysed for presence of seizures and 46 were analysed for background discontinuity. Sensitivity for presence of seizures by aEEG was 80% and specificity was 50%. The proportion of infants with seizures were overdiagnosed by aEEG (63.6% vs 45.5% for sEEG p=0.045). Discontinuity of background activity had higher sensitivity (88.6%) and specificity (54.5%) when compared with seizure detection. When stratified by indication for EEG, hypoxic episode (n=14) or suspected seizures (n=33), similar sensitivity for presence of seizure (80%) was noted by aEEG and sEEG. However the specificity of aEEG for seizure detection was higher in neonates undergoing EEG for suspected seizures (66.7% vs 22.2%). Conclusions: Background abnormalities were detected with fair accuracy by aEEG but aEEG criteria alone would result in the overdiagnosis of neonatal seizures. Therefore seizures noted on aEEG require sEEG confirmation prior to implementing anticonvulsant therapy for neonatal seizures.